SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN BANDENG DURI LUNAK DI TOKO BANDENG JUWANA KOTA SEMARANG - Gary Yefta Herbeth Siagian; Wiludjeng Roessali; Tri Winarni Agustini (Universitas Teuku Umar, 2018)
The aims of this study were to analyze consumer attitude, to know the factors which influences buyer attitude toward decision of purchase of softbone milkfish, and to study on satisfaction toward attribute’s of softbone milkfish at Juwana milkfish shop in Semarang City. The methods of this study were survey. The methods used were an accidental sampling of 100 respondents. The data were analyzed of using Fishbein, Important Performance Analisis (IPA), Customer Satisfaction Index (CSI), and multiple linear regression. The result of this study showed that attitude of customer assessing of milkfish production for TBJ is positive with a score of 19.52. This means that consumer feels the attribute’s of milkfish a comply with customer. Need factors that influence consumer attitudes towards purchasing decision in TBJ very significantly influenced by their job and income. The job status are government employees signicficantly buyer descision. Descision buyers average is on range Rp. 2.000.000-Rp.4.000.000 with average account the buyers most of 4-8 kg/month. Another variable of gender, education level, and location had no significant effect to purchasing decision. The level of customer satisfaction in TBJ that is on categories of satisfied with a value of 0,72. This means that the company's performance in providing products are in accordance with customer expectations